Bolehkah Gereja Berpengadilan? - Jan Sihar Aritonang (Theologia in Loco, 2020)
The Christian Church, throughout its history, has involved in various kinds of cases with multiple variants. This paper presents a historical explanation, in a limited way, the church’s journey with the issue of the court with various considerations from the fieldsof ethics, ecclesiology, and pastoral. In the end, I argued that the church needed - even needed - to bring several cases to court, such as criminal acts, including misappropriation of positions, including financial and asset matters. Or on issues of struggle to uphold justice, human rights, discrimination, intolerance, the church must process it to the court.